2017
DOI: 10.1177/000313481708301201
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing Improvement Project—A Resident Run Success

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It has been shown that implementing accountability, reward incentives, or goal setting may help sustain high compliance rates [10,14]. However, few studies reported on ownership of hand hygiene surveillance by physicians or nurses, all revealing a significant positive impact on compliance rates [15][16][17][18][19], The sustainability of high compliance rates in our setting may be attributed to the motivated physicians in charge of surveillance who may have felt that it was their responsibility to achieve the set goal. Physicians are the least involved in quality improvement initiatives, mainly because of time constraints and other work priorities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that implementing accountability, reward incentives, or goal setting may help sustain high compliance rates [10,14]. However, few studies reported on ownership of hand hygiene surveillance by physicians or nurses, all revealing a significant positive impact on compliance rates [15][16][17][18][19], The sustainability of high compliance rates in our setting may be attributed to the motivated physicians in charge of surveillance who may have felt that it was their responsibility to achieve the set goal. Physicians are the least involved in quality improvement initiatives, mainly because of time constraints and other work priorities.…”
Section: Discussionmentioning
confidence: 92%
“…We found this experience to be useful since it saves on institutional human resources, is reliable, and sensitizes the students to the importance of proper hand hygiene for patient safety early on in their career. Rees et al [ 27 ] and Ghee & Kowdley [ 17 ] also depended on volunteer medical students to implement their hand hygiene initiatives with similar success. A second limitation of our initiative is that some health care workers may be uncomfortable in reporting non-compliant colleagues or supervisors, especially in units with a small number of staff.…”
Section: Discussionmentioning
confidence: 99%
“…Fung and Cairncross [21] observed a decline in the practice of this preventative measure. To avoid such a decline and other errors, it is imperative to implement methods that successfully achieve correct preventative handwashing [44].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Fung et al also observed a decline of practice of this preventive measure 14 . Therefore, in order to avoid this decline and errors, we must implement methods to successfully achieve a correct preventive handwashing 39 .…”
Section: Discussionmentioning
confidence: 99%